2017
DOI: 10.1016/j.heares.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Loudness and pitch perception using Dynamically Compensated Virtual Channels

Abstract: Reducing power consumption is important for the development of smaller cochlear implant (CI) speech processors. Simultaneous electrode stimulation may improve power efficiency by minimizing the required current applied to a given electrode. Simultaneous in-phase stimulation on adjacent electrodes (i.e. virtual channels) can be used to elicit pitch percepts intermediate to the ones provided by each of the physical electrodes in isolation. Virtual channels are typically implemented in monopolar stimulation mode,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, only Arenberg et al (2018) and Nogueira et al (2017) have investigated similar dynamic focusing configurations, although Nogueira’s work involved virtual channels and added current steering through quadrupolar stimulation instead of physical electrodes. Because Nogueira et al combined focusing with steering and did not conduct speech or spectro-temporal testing, we cannot directly compare the performance of their strategy to the dynamic strategies of Arenberg (2018) and de Jong (2019a, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only Arenberg et al (2018) and Nogueira et al (2017) have investigated similar dynamic focusing configurations, although Nogueira’s work involved virtual channels and added current steering through quadrupolar stimulation instead of physical electrodes. Because Nogueira et al combined focusing with steering and did not conduct speech or spectro-temporal testing, we cannot directly compare the performance of their strategy to the dynamic strategies of Arenberg (2018) and de Jong (2019a, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reduced level of current focusing, pTP stimulation improves spectral ripple discrimination (Berenstein et al 2008;Smith et al 2013), while speech perception showed to be improved in some (Srinivasan et al 2013;Wu & Luo 2013), but not in all studies (Berenstein et al 2008;Bierer & Litvak 2016). Nogueira et al (2017) developed a stimulation mode called the dynamically compensated virtual channel in which four adjacent electrodes are stimulated simultaneously to decrease power consumption. Although this quadrupolar strategy saves power, it also generates broader electrical fields, specifically at higher loudness levels.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different computational models of CIs that have been fitted using clinical data, such as transimpedances, cochlear dimensions, electrode locations, and loudness and pitch perception [ 10 , 25 , 27 , 28 ], and speech understanding [ 29 ]. Additionally, there are other models that simulate ECAPs responses [ 14 , 16 , 22 , 30 32 ] as the one proposed in this work.…”
Section: Introductionmentioning
confidence: 99%